2017
DOI: 10.1128/jcm.02221-16
|View full text |Cite
|
Sign up to set email alerts
|

Coelomycetous Fungi in the Clinical Setting: Morphological Convergence and Cryptic Diversity

Abstract: Human infections by coelomycetous fungi are becoming more frequent and range from superficial to systemic dissemination. Traumatic implantation of contaminated plant material is the most common cause. The typical morphological feature of these fungi is the production of asexual spores (conidia) within fruiting bodies called conidiomata. This study aimed to determine the distribution of the coelomycetes in clinical samples by a phenotypic and molecular study of a large set of isolates received from a U.S. refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 63 publications
5
65
2
Order By: Relevance
“…This study utilized a mixture of historical eumycetoma agents and more recent isolates from imported cases of eumycetoma stored in NCPF, and the organisms utilized thus reflect those organisms encountered most frequently in the United Kingdom. While it does not cover the full spectrum of eumycetomal organisms, pleosporalean fungi were predominant among the eumycetomal organisms in our collection, in agreement with the findings of a variety of previous studies (12,13,21,26,33). Moreover, given the high log scores achieved with the organisms included here, coupled with the absence of an obvious overlap between spectral profiles (the next best matches were against unrelated organisms and had only very poor scores), we believe that the retrieval of reliable and unique MSPs should also be possible with mycetoma agents that are underrepresented or absent from the current study.…”
Section: Discussionsupporting
confidence: 80%
“…This study utilized a mixture of historical eumycetoma agents and more recent isolates from imported cases of eumycetoma stored in NCPF, and the organisms utilized thus reflect those organisms encountered most frequently in the United Kingdom. While it does not cover the full spectrum of eumycetomal organisms, pleosporalean fungi were predominant among the eumycetomal organisms in our collection, in agreement with the findings of a variety of previous studies (12,13,21,26,33). Moreover, given the high log scores achieved with the organisms included here, coupled with the absence of an obvious overlap between spectral profiles (the next best matches were against unrelated organisms and had only very poor scores), we believe that the retrieval of reliable and unique MSPs should also be possible with mycetoma agents that are underrepresented or absent from the current study.…”
Section: Discussionsupporting
confidence: 80%
“…[4,7,34]. Thus, results of the in vitro susceptibility testing with these fungi should be interpreted very carefully.…”
Section: Discussionmentioning
confidence: 99%
“…The taxonomy of the genera is still very problematic and has been constantly revised [2][3][4]. These fungal species are worldwide distributed in tropical and subtropical regions and are principally known as phytopathogens but some species can infect humans via direct contact with colonized plants [1].…”
Section: Introductionmentioning
confidence: 99%
“…Morphological identification of M romeroi, a coelomycetous fungus uncommonly isolated in Western countries, is difficult and requires mycological expertise. Clinical isolates often fail to produce characteristic structures such as pycnidia in culture media, and molecular techniques available in reference mycology laboratories (ie, sequencing only of specific fungal regions) may be needed to achieve reliable identification . The isolates from our clinical report and those of the literature review were all identified by molecular sequencing, highlighting the importance of these tests for identifying uncommon melanized fungi such as M romeroi .…”
Section: Discussionmentioning
confidence: 99%